Penyuluhan dan praktek pembuatan pakan komplit fermentasi kepada peternak sapi dan kerbau di Aceh Jaya (Counseling and training on preparation of fermentation complete feed for cow and buffalo farmers in Aceh Jaya) - Usman, Yunasri; Wajizah, Siti; Allaily, A (Universitas Syiah Kuala, 2021)
This community service activity aimed to introduce the methods for formulating complete feed with fermentation technology to the local farmers. This activity was targeted to farmers community in Keude Panga Village, Aceh Jaya Regency, Aceh Province. This community service was attended by 3 lecturers, 25 participants, and a number of representatives from related service officials. The activity was carried out by giving lecture, discussion (for 1 day) and hands-on training on complete fermented feed preparation for 21 days. The processing introduced was in the form of fermentation technology using materials such as elephant grass, lamtoro (Chinese petai) leaves, coconut cake, tofu dregs, coarse bran, urea, molasses, salt, and effective microorganisms (EM-4) which were then formulated into a complete feed. The ingredients used were locally available in Aceh in general and also available at the Laboratory of Nutrition Science and Feed Technology, Department of Animal Husbandry, Faculty of Agriculture, Universitas Syiah Kuala, Darussalam, Banda Aceh. As a result, farmers could gain additional knowledge and skills about feed processing with fermentation technology using local feed ingredients. In conclusion, it is suggested that the farmers can take advantage on agricultural and industrial wastes in the vicinity, whose nutritional potential can be maintained and improved by fermentation technology.